Hukum Islam Pada Masa Awal Masuknya Islam Ke Nusantara - Usqo, Hanafi Urwatil; Fuad, Zainul; Sarumpaet, M. Idris (Jurnal Ilmu Sosial, Humaniora dan Seni, 2024)
In fact, Islam Nusantara is not something new. The bolding of the word "Nusantara" combined with "Islam" not only emphasizes the name, but also the character to show the pattern or color of a heterogeneous entity. In the past, Indonesia was known as the archipelago, but now it has changed because it has become a sovereign unitary state. Indonesia is also one of the largest places for the Islamic religion with the most adherents, which has its own unique characteristics in the history of its development. Indonesian Islam is spread, taught and adhered to in a peaceful and well-received manner. In the process of Islam entering the archipelago, there were several theoretical debates. This diversity of theories occurs because we look at the current conditions and realities of Muslims in the archipelago. Indications of religious practices, historical heritage and even customs carried out by Indonesian Muslims are important indicators to answer the first arrival of Islam. The entry of Islam into the archipelago brought by merchants, Sufis and ulama had its own characteristics starting from economic, political, educational, and even accommodating local culture. Introducing Islam as a new religion to people who already have animist beliefs, dynamism and have embraced Hinduism and Buddhism makes the ulama take a cultural approach. Apart from displaying good morals, the ulama in their daily lives also carry out acculturation to culture and even religion and community beliefs to introduce, teach and preach peaceful Islam. This cultural acculturation then makes Islam as a new religion easy to understand, accept and follow by society